Risk factors and management for early and late intrahepatic recurrence of solitary hepatocellular carcinoma after curative resection. Issue 5 (24th November 2014) - Cheng, Zhangjun; Yang, Pinghua; Qu, Shuping; Zhou, Jiahua; Yang, Jue; Yang, Xinwei; Xia, Yong; Li, Jun; Wang, Kui; Yan, Zhenlin; Wu, Dong; Zhang, Baohua; et al.
Abstract Background Intrahepatic recurrence is a significant problem for patients who have undergone a hepatic resection for hepatocellular carcinoma (HCC). The objective of the present study was to identify risk factors and evaluate the management of early and late recurrence of solitary HCC after curative resection. Methods Included in this study were 816 patients with solitary HCC who underwent a curative partial hepatectomy. Intrahepatic recurrence in these patients was followed up retrospectively. Prognosis and therapy for the recurrence were investigated and analysed. Results Early and late intrahepatic recurrence occurred in 423 patients and 199 patients, respectively. Multivariate analysis showed that a tumour diameter >5 cm, the absence of a tumour capsule and the presence of microvascular invasion were correlated with early recurrence, whereas cirrhosis and alpha‐fetal protein >400 μg/l were independent risk factors contributing to late recurrence. The 5‐year survival of HCC patients with early recurrence was significantly lower than that of patients with late recurrence. Further curative treatment for intrahepatic recurrence offered a 5‐year overall survival of 56.0%, which was better than alternative management. Conclusion Early and late recurrences of solitary HCC after curative resection are associated with different predictive factors. The time to recurrence and further curative treatment after recurrence were the best predictors of survival post recurrence.